Microalbuminuria in the Early Diagnosis of Kidney Damage in Diabetic Patients - Gabriel Ignacio Hinojoza Alarcón; Agustín Paramio Rodríguez (Revista Finlay)
Background: the early detection of microalbuminuria in diabetic patients is considered the best and earliest marker of diabetic nephropathy. It is currently considered as a marker of endothelial dysfunction and vascular disease. Objective: to determine the behavior of microalbuminuria in diabetic patients belonging to the medical office 25 of the Presidente Salvador Allende Teaching Community Polyclinic in Havana. Methods: a descriptive cross-sectional study was carried out. The universe was made up of 1125 people belonging to the medical office. The sample consisted of 62 patients with diabetes mellitus. The study was carried out from January to December 2018. The diagnosis of microalbuminuria was made after it was verified in two determinations of the three carried out in a period of 6 months, with two groups of patients being constituted according to whether the microalbuminuria presence or not was determined. Results: the 11.3 % of the diabetic patients presented microalbuminuria. The presence of microalbuminuria was higher in males (12.9 %), in those older than or equal to 70 years old (21.4 %), in diabetics with a disease evolution time of 20 or more years (18, 7 %), in patients with insulin-dependent diabetes mellitus (50 %) and in patients with severe lack of control of the disease (55.6 %). Conclusions: microalbuminuria predominates in older diabetic patients it is related to the diabetes mellitus evolution time. It is related to metabolic control. It is more common in patients with insulin-dependent diabetes mellitus.